The effects of rotation speed and friction time for joining of AISI 4340-2205 steels by friction welding - Caligulu, U.; Yalcinoz, M.; Kati, N.; Balalan, Z.; Islak, S. (Palladin Institute of Biochemistry of the NASU, 2015)
Friction welding is a solid state joining process used extensively currently owing to its advantages such as low heat input, high production efficiency, ease of manufacture, and environment friendliness. Materials difficult to be welded by fusion welding processes can be successfully welded by friction welding. In the fusion welding methods for joining different materials, brittle intermetallic compounds phases are produced in the fusion zone, which reduces the strength of the welding joint. In this study, the effects of rotation speed and friction time for joining of AISI 4340-2205 steels welded by friction are investigated. Specimens of AISI 4340 tempered steel and AISI 2205 duplex stainless steel, each of 12 mm diameters, are used to fabricate the joints. The friction welding tests are carried out using a direct-drive type friction-welding machine, which was designed and manufactured for this purpose by us. After friction welding, in order to determine the occurred microstructural changes, the interface regions of the welded specimens are examined by means of OM, SEM, EDS and X-Ray analysis. Microhardness and tensile tests are conducted to determine the mechanical properties of the welded specimens. The experimental results indicate that AISI 4340 tempered steel could be joined to AISI 2205 duplex stainless steel using the friction welding technique and for achieving a weld with sufficient strength. Tensile strength values also confirm this result, and, at the interface, intermetallic phases do not occurred. The maximum tensile strength of 635.66 MPa could be obtained for the joints welded under the welding conditions of rotation speed of 2200 rpm, friction pressure of 40 MPa, forging pressure of 80 MPa, friction time of 6 s, and forging time of 3 s.
Keywords: AISI 2205; AISI 4340; Friction time; Friction welding; Rotation speed